2008
DOI: 10.1243/03093247jsa320
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behaviour of high‐strength sheet steel in dynamic tension: Experimental and numerical analyses

Abstract: This paper presents the behaviour of high-strength steel TRIP 700, frequently applied in automotive industries. This material is used to design some car components owing to high stress levels induced by phase transformation. Generally, a pre-plastic deformation is induced in the sheet steel at a low strain rate to transform austenite into martensite. The next step is to design for example a crash box, as described previously by Durrenberger et al. [1], in order to increase the level of energy absorption. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Zwick). A wide range of strain rates was covered at room temperature, Rusinek et al [13,14] showed that these dimensions of the tensile specimens ( Fig. 1) are optimum, which allows to achieve a proper level of stress coupled with sufficient ductility.…”
Section: Experimental Materials Behavior Descriptionmentioning
confidence: 99%
“…Zwick). A wide range of strain rates was covered at room temperature, Rusinek et al [13,14] showed that these dimensions of the tensile specimens ( Fig. 1) are optimum, which allows to achieve a proper level of stress coupled with sufficient ductility.…”
Section: Experimental Materials Behavior Descriptionmentioning
confidence: 99%
“…This algorithm belongs to the class called return mapping, which are robust and widely used in practice (Simo and Ortiz, 1985;Simo and Taylor, 1986). The algo rithm was previously implemented into RK scheme in or der to simulate impact problems like dynamic tension test (Rusinek et al, 2005(Rusinek et al, , 2008a, dynamic ring expansion (Rusinek at al., 2007b) and perforation processes (Rusinek et al, 2008c). In the previous numerical work, (Rusinek et al, 2008c), several constitutive relations were evaluated, namely: PL, JC and RK.…”
Section: A Role Of Constitutive Relationmentioning
confidence: 99%
“…Nowadays several publications can be found in the international literature dealing with high strain rate behaviour of different metallic materials directly related to engineering applications like automotive (Rusinek et al, 2008a;Larour et al, 2007;Mae et al, 2007;Smerd et al, 2005), civil (Kobayashi et al, 2008;Shanmugama et al, in press;Zaera et al, 2002), aeronautical (Fasanella and Jackson, 2001;Piekutowski, 1999) or naval (Nemat Nasser and Guo, 2003;Martineau et al, 2004) industries. Particularly, the behaviour of high strength sheet metals 1 when subjected to high velocity impact by rigid projectiles has raised a considerable interest as it is illustrated in the works (Borvik et al, 2002a,b;Gupta et al, 2006Gupta et al, , 2007Ar ias et al, 2008;Rusinek et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…In [7,8] the influence of the length to diameter ratio of the cylindrical specimens used in compression experiments is discussed and clear recommendations are given to minimise inertial and frictional effects. For tensile Hopkinson experiments, dogbone-shaped specimens are generally used; however, no agreement exists on the exact dimensions [9,10].…”
Section: Introductionmentioning
confidence: 99%